2015
DOI: 10.1021/jacs.5b03651
|View full text |Cite
|
Sign up to set email alerts
|

The Real Role of N-Heterocyclic Carbene in Reductive Functionalization of CO2: An Alternative Understanding from Density Functional Theory Study

Abstract: The mechanisms of reductive functionalization of CO 2 to formamide catalyzed by N-heterocyclic carbene (NHC) were comprehensively studied with DFT calculations. New activation mode with much lower energy barrier than those proposed before was discovered. In this reaction, NHC acts as neither a CO 2 nor a silane activator, but as a precursor of the real catalyst, i.e., the in situ formed ionic liquid [NHCH] + [Carbamate] -. In this loose contact ion pair, the negatively charged O atom of the carbamate anion bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 93 publications
(30 reference statements)
11
96
0
Order By: Relevance
“…With polymethylhydrosiloxane (PMHS), an N‐formylation product was not observed, and instead, cross‐linking of the polymer occurred. The decrease in the reaction rate observed with Ph 2 SiH 2 is consistent with the proposed S N 2‐type mechanism for the reaction of hydrosilanes with hydroxide anions and the calculated S N 2‐type mechanism for CO 2 reduction with silicon hydride, as well as the formation of an axial silicon hydride bond. The steric congestion induced by an additional phenyl ring hinders nucleophilic attack by the anion on the silicon center and prevents its activation.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…With polymethylhydrosiloxane (PMHS), an N‐formylation product was not observed, and instead, cross‐linking of the polymer occurred. The decrease in the reaction rate observed with Ph 2 SiH 2 is consistent with the proposed S N 2‐type mechanism for the reaction of hydrosilanes with hydroxide anions and the calculated S N 2‐type mechanism for CO 2 reduction with silicon hydride, as well as the formation of an axial silicon hydride bond. The steric congestion induced by an additional phenyl ring hinders nucleophilic attack by the anion on the silicon center and prevents its activation.…”
Section: Methodssupporting
confidence: 85%
“…A number of different CO 2 reduction mechanisms are possible by the silicon hydride. However, whereas direct CO 2 insertion into the polarized Si δ + −H δ − bond was previously suggested and is partly supported by the detection of the hypervalent silicon intermediate, a recent DFT study of related systems indicated that in the presence of CO 2 a concerted hydride transfer proceeding though an S N 2‐type mechanism with a structurally equivalent five‐coordinate silicon transition state followed by reinsertion of a formate anion was energetically favored …”
Section: Methodsmentioning
confidence: 94%
“…Theoretical studies on organocatalyzed CO 2 functionalization reactions can be used to reveal mechanistic details at the molecular level . Furthermore, in certain cases, calculations can be used to reveal novel activation modes . With this in mind, we envisaged that density functional theory (DFT) calculations could be used to elucidate the mechanism of this useful guanidine‐catalyzed CO 2 transformation.…”
Section: Introductionsupporting
confidence: 90%
“…The first example of metal-free catalytic reduction of carbon dioxide was reported by Ying and coworkers in 2009 when they demonstrated that N-heterocyclic carbenes can catalyze the hydrosilylation of CO2 to methoxysilanes [52]. While the mechanism is debated [53][54], recently published computations suggest that the NHC-CO2 adduct serves as a Lewis base in order to activate silanes by hyper-coordination, thus favoring hydride transfer [55]. In that regard, we also reported that phosphazenes could act as efficient catalysts for CO2…”
Section: Rationalizing the Catalytic Activity Of Ambiphilic Moleculesmentioning
confidence: 99%